DEVELOPMENT AND VALIDATION OF A STABILITY INDICATING RELATED SUBSTANCES OF TRANDOLAPRIL BY RP-HPLC AND ITS DEGRADATION - REDDY, CHALLA SUDHEER; RAO, B. TIRUMALESWARA (International Journal of Applied Pharmaceutics, 2021)
Objective: A validated stability-indicating RP-HPLC method for Trandolapril was developed by separating its related impurities. Methods: By using Waters HPLC e-2695 quaternary pump with a PDA detector of 2998 instrument the chromatographic separation of Trandolapril and its related impurities was achieved on the column of Agilent eclipse C18 (150x4.6 mm, 3.5 µ) using gradient elution with a buffer containing 0.1percent formic acid and acetonitrile as a mobile phase with a flow rate of 1 ml/min at ambient temperature. A detector wavelength of 213 nm utilizing the PDA detector were given in the instrumental settings. The linearity was studied between the concentration range of 4-60 µg/ml of Trandolapril and 0.5-7.5 µg/ml of imp-E, imp-A, imp-B and 0.7-10.5 µg/ml of imp-D were injected with a run time of 17 min. Validation of the proposed method was carried out according to an International Conference on Harmonization (ICH) guidelines. Results: LOD and LOQ for the Trandolapril and its impurities were established with respect to test concentration. The plotted calibration curves were linear with a regression coefficient of R2>0.999, indicates that the linearity was with in the limit. As a part of method validation the parameters like specificity, linearity, accuracy, ruggedness, robustness were determined and the results were found to be within the allowable limit. Conclusion: The method developed was found to be applicable to routine analysis and to be used for the measurement of active pharmaceutical ingredients (i. e, Trandolapril and its related impurities). Since, there is no HPLC method reported in the literature for the estimation of Trandolapril and its related impurities, there is a need to develop quantitative methods under different conditions to achieve improvement in specificity, selecivity etc.